2022
DOI: 10.1007/s11356-022-21204-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling of tetracycline degradation in water in a flow-through enzymatic monolithic reactor

Abstract: In this work, the laccase from Trametes versicolor was immobilized in highly porous silica monoliths (0.6 cm diameter, 0.5 cm length). These monoliths feature a unique homogeneous network of interconnected macropores (20 μm) with mesopores (20 nm) in the skeleton and a high specific surface area (330 m 2 /g). The enzymatic monoliths were applied to degrade tetracycline (TC) in model aqueous solutions (20 ppm). For this purpose, a tubular Flow-Through-Reactor (FTR) configuration with recycling was built. The TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…[14] In Figure 2 flow rate of 1 mL min −1 with continuous recycling. [15] They found that 40%-50% of tetracycline was degraded in 5 h. Additionally, the silica monolith immobilized laccase presented high operational stability during 75 h which, according to the authors, indicated the applicability of the developed reactors on a large scale. However, the scalability of such minireactors is a matter to be researched.…”
Section: Immobilized-laccase Bioreactors For Wastewater Treatmentmentioning
confidence: 83%
“…[14] In Figure 2 flow rate of 1 mL min −1 with continuous recycling. [15] They found that 40%-50% of tetracycline was degraded in 5 h. Additionally, the silica monolith immobilized laccase presented high operational stability during 75 h which, according to the authors, indicated the applicability of the developed reactors on a large scale. However, the scalability of such minireactors is a matter to be researched.…”
Section: Immobilized-laccase Bioreactors For Wastewater Treatmentmentioning
confidence: 83%